2022
DOI: 10.3390/molecules27020539
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer and Antibiotic Rhenium Tri- and Dicarbonyl Complexes: Current Research and Future Perspectives

Abstract: Organometallic compounds are increasingly recognized as promising anticancer and antibiotic drug candidates. Among the transition metal ions investigated for these purposes, rhenium occupies a special role. Its tri- and dicarbonyl complexes, in particular, attract continuous attention due to their relative ease of preparation, stability and unique photophysical and luminescent properties that allow the combination of diagnostic and therapeutic purposes, thereby permitting, e.g., molecules to be tracked within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 146 publications
0
30
0
Order By: Relevance
“…This was characterized as C14H10N2O. 10 Isatin (5 g; 0.03398 mol) was completely dissolved with 200 ml methanol and sulphanilamide (5.85 g; 0.03398 mol) was also added, while room temperature synthesis was being carried out. After which 8 drops of concentrated H2SO4 was also added and stirred for 1 1 /2 h. Filtration of the yellow product was followed with recrystallization in ethanol: chloroform (70: 30).…”
Section: Preparation Of the Isatin Schiff Basementioning
confidence: 99%
“…This was characterized as C14H10N2O. 10 Isatin (5 g; 0.03398 mol) was completely dissolved with 200 ml methanol and sulphanilamide (5.85 g; 0.03398 mol) was also added, while room temperature synthesis was being carried out. After which 8 drops of concentrated H2SO4 was also added and stirred for 1 1 /2 h. Filtration of the yellow product was followed with recrystallization in ethanol: chloroform (70: 30).…”
Section: Preparation Of the Isatin Schiff Basementioning
confidence: 99%
“…[11] In recent decades, many attempts have been made to optimize the structure of nonplatinum based metal complexes in order to improve their curative effect. Among them, the complexes of gold, [12] ruthenium, [13] iridium [14] and rhenium [15] are the most prominent ones for the construction of anticancer platforms. Compared with the existing platinum-based anticancer drugs, these complexes have clearly shown interesting anticancer properties and alternative action mechanisms, such as increasing selectivity for cancer cells and being activated by visible light or even near-infrared light.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown the potent anticancer activity of rhenium complexes. The most active rhenium compounds reported to date contain Re­(I) tricarbonyl centers bound to mono-, di-, or tridentate ligands, suggesting that their cytotoxicity is due to covalent interactions with DNA bases and/or protein side chains. Various researchers are trying to establish the mechanism of action for rhenium complexes with the same core through computational tools. Zobi and collaborators experimentally and computationally determined the union of different nitrogenous bases with a rhenium complex.…”
Section: Introductionmentioning
confidence: 99%